Mekanisme Resiliensi Qur-ani: Analisis Munasabah Surah Ad-Dhuha dan al-Insyirah: Intertextual Resilience in the Quran: A Munasabah Perspective on Surah Ad-Duha and Al-Inshirah - Alawy Abdillah (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2026)
Amid the rising global mental health crisis, this study aims to construct a systematic model of resilience mechanisms derived from the Quran, moving beyond previous conceptual studies that tend to focus primarily on moral values. This research addresses that gap by analyzing the structural and thematic coherence (munasabah) between Surah Ad-Duha and Al-Inshirah. Using a qualitative library-based approach, the study synthesizes interpretations of authoritative classical scholars such as ar-Razi and al-Biqai with concepts from Islamic psychology and modern psychological frameworks, including Cognitive Restructuring and Behavioral Activation. The main findings indicate that these two surahs form a systematic recovery mechanism consisting of three progressive stages: (1) Tasbit al-Fuad (Crisis Stabilization), which emphasizes acceptance, consolation, and hope; (2) Syukur al-Faal (Narrative Reconciliation), achieved through reflection on past blessings and prosocial action; and (3) Mujahadah Daimah (Growth Activation), which involves strengthening inner capacity, reinforcing conviction, and activating continuous purposeful action to prevent post-crisis stagnation. This model implies a shift in understanding the Quran from merely a source of ethical guidance to a functional framework for psychological recovery processes, offering conceptually applicable insights for contemporary society.